Klasa społeczna ucznia a afordancje w nauce języka angielskiego - Aleksiejuk, Joanna (Neofilolog, 2025)
Although factors promoting success in foreign language learning have long been the object of scholarly interest in the field of language education, little attention has been devoted to the role of social factors, such as the learner’s social class, in the Polish literature. Drawing on the work of sociologists of education and using the theory formulated by French sociologist Pierre Bourdieu, the study aims to shed light on the disparities between learners from the popular class and the middle class in relation to their access to affordances for learning English as a foreign language. The research comprised an online questionnaire (N = 32) and semi-structured interviews (N = 8) carried out among secondary students of English as a foreign language attending a vocational school and a private grammar school catering mainly to the popular and middle class respectively. The results show significant differences in the affordances supplied by the students’ families. Most notably, students from the middle class have access to more varied and long-term extracurricular English classes and have more opportunities to use the language in the natural setting while travelling abroad. They also receive more encouragement and support from their parents, who actively engage in creating affordances for learning.